Geographical distribution and driving force of microbial communities in the sediments of Diamantina and Kermadec trenches - Zhang, Yue; Jing, Hongmei; Liu, Hao (Frontiers in Microbiology, 2024)
The distinctive geological characteristics of hadal trenches are recognized to affect the construction and ecological role of microbial communities; however, information on their population dynamics and assembly processes remains limited. In this study, bacteria and micro-eukaryotes in the sediments of the Diamantina and Kermadec trenches were explored utilizing high-throughput sequencing. Compared to the Diamantina Trench, significantly lower levels of bacterial and micro-eukaryotic biodiversity (p < 0.01), bacterial gene copy number (p < 0.05), and heterotrophic/parasitic micro-eukaryotic proportions (p < 0.05) were detected in the Kermadec Trench, which also exhibited a low community complexity based on the network analysis. Within each trench, no obvious population shifts were observed along the trench axis. Microbial communities in both trenches showed clear distance–decay distributions, mainly driven by stochastic processes. This study provided fresh perspectives on the microbial community assembly mechanism in deep-sea trenches. Studies of community complexity and diversified trophic states of microbes would contribute to an improved understanding of ecological functions and diversification in this extreme biosphere.